2013
DOI: 10.1021/jm400645w
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoyl Pyridone HIV-1 Integrase Inhibitors 3. A Diastereomeric Approach to Chiral Nonracemic Tricyclic Ring Systems and the Discovery of Dolutegravir (S/GSK1349572) and (S/GSK1265744)

Abstract: We report herein the discovery of the human immunodeficiency virus type-1 (HIV-1) integrase inhibitors dolutegravir (S/GSK1349572) (3) and S/GSK1265744 (4). These drugs stem from a series of carbamoyl pyridone analogues designed using a two-metal chelation model of the integrase catalytic active site. Structure-activity studies evolved a tricyclic series of carbamoyl pyridines that demonstrated properties indicative of once-daily dosing and superior potency against resistant viral strains. An inherent hemiamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
138
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 28 publications
0
138
0
Order By: Relevance
“…DTG was designed to maintain activity against many INSTI-resistant mutants with single or multiple substitutions (20,(31)(32)(33)(34)(35), and this is consistent with biochemical and structural observations (36,37). Studies showed that the dissociation half-life of DTG from IN/ substrate-DNA/INSTI triple complex in the presence of the amino acid substitutions Q148H, Q148K, or Q148R and N155H significantly reduced the dissociation half-life from that of wildtype IN but was still similar to that of RAL to wild-type IN.…”
Section: Resultsmentioning
confidence: 99%
“…DTG was designed to maintain activity against many INSTI-resistant mutants with single or multiple substitutions (20,(31)(32)(33)(34)(35), and this is consistent with biochemical and structural observations (36,37). Studies showed that the dissociation half-life of DTG from IN/ substrate-DNA/INSTI triple complex in the presence of the amino acid substitutions Q148H, Q148K, or Q148R and N155H significantly reduced the dissociation half-life from that of wildtype IN but was still similar to that of RAL to wild-type IN.…”
Section: Resultsmentioning
confidence: 99%
“…This flexibility is reminiscent of what is seen with 2 , where the flexibility of the haloamide component is thought to contribute to the ability of 2 to maintain efficacy against certain forms of IN that are resistant to 1 . 1820 …”
Section: Resultsmentioning
confidence: 99%
“…They contain a two-metal binding pharmacophore consisting of a carbamoyl pyridone moiety (see Fig. 1) and were optimized to deliver the attributes that would differentiate them as new INSTIs (14,15). Clinical data for GSK1265744 administered to healthy subjects and HIV patients present a PK profile supporting once-daily oral administration from a low-milligram dose, with low PK variability and excellent short-term safety/tolerability, as well as highly effective anti-HIV activity from 10 days of monotherapy (16).…”
mentioning
confidence: 99%